On the prediction of complex shear dominated concrete failure by means of classical and higher order damage-plasticity continuum models. (15th January 2022) - Neuner, M.; Hofer, P.; Hofstetter, G.
Abstract: In the present contribution, the capabilities of classical and higher order damage-plasticity continuum models in their ability to predict complex shear failure of concrete is assessed. To this end, a classical local formulation of the popular Concrete Damage-Plasticity model by Grassl and Jirásek (2006a) with mesh-adjusted softening modulus is compared to a higher order gradient-enhanced formulation by Poh and Swaddiwudhipong (2009) and a recently proposed gradient-enhanced micropolar formulation by Neuner et al. (2020a) by means of challenging 3D finite element simulations of a transverse shear test. The transverse shear test is characterized by an anchor channel embedded in a concrete slab, which is loaded transversely to its axis until failure. A comparison with experimental results highlights the limitations of classical local formulations, whereas higher order continuum approaches show great potential in particular for modeling the structural post-peak response. Highlights: Classical and higher-order damage-plasticity models for concrete are reviewed 3D finite element analysis of a challenging transverse shear test on anchor channels Shortcomings of predictive capabilities of classical models are demonstrated The capabilities of higher-order models are highlighted Post-peak behavior is best predicted by a gradient-enhanced micropolar model